War and rumours of war, do improvements in space technologies bring space conflict closer?. Issue 2 (3rd April 2018) - Handberg, Roger
ABSTRACT: Combat in near-Earth orbit is emerging as a more realistic possibility. The argument here is that changes in space technologies combined with a sea change in political rhetoric is bringing the possibility of military conflict in space technologies. This movement reflects a generational shift as the original decisions regarding military conflict in space are now being reassessed by a generation who did not experience World War II or the Cold War. For these, the sanctuary approach to space activities is not as persuasive and new enhanced space technologies bring the possibility of victory or at least survival possible during a conflict in space.